2017
DOI: 10.3892/ol.2017.7485
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin increases anticancer effects of lentinan in HepG2 human hepatoblastoma cells

Abstract: Abstract. The aim of the present study was to investigate whether oridonin is able to increase the effects of lentinan (LNT) in HepG2 human hepatoblastoma cells by MTT, flow cytometry, reverse transcription-quantitative polymerase chain reaction and western blot analysis. The in vitro results demonstrated that 20 µg/ml of oridonin was a nontoxic concentration for L02 normal liver cells and HepG2 liver cancer cells. Furthermore, treatment with 0-200 µg/ml LNT was only able to decrease the viability of HepG2 liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A wide variety of sources have reported the anticancer mechanism of oridonin in multiple cancer cell lines [17,24,27,[29][30][31][32]. According to the study of Yao et al (2017) oridonin induced autophagy by decreasing the protein levels of glucose transporter 1 (GLUT1) and monocarboxylate transporter 1 (MCT1) in SW480 human colorectal cancer cells, in the BALB/c xenograft model.…”
Section: Oridoninmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of sources have reported the anticancer mechanism of oridonin in multiple cancer cell lines [17,24,27,[29][30][31][32]. According to the study of Yao et al (2017) oridonin induced autophagy by decreasing the protein levels of glucose transporter 1 (GLUT1) and monocarboxylate transporter 1 (MCT1) in SW480 human colorectal cancer cells, in the BALB/c xenograft model.…”
Section: Oridoninmentioning
confidence: 99%
“…Moreover, it inhibited the expression of phosphoinositide 3-kinase (PI3K) and blocked phosphorylation of protein kinase B (p-Akt). Sun et al (2018) reported synergistic anticancer activity of oridonin in combination with lentinan by decreasing the expression of BCL-2 and nuclear factor kappa B (NF-κB) and increasing the expression of caspase-3, -9, p53, p21, NF-κB inhibitor-α (IκB-α) by increasing transcription of mRNA and translation of the mRNA into their respective protein products in human hepatoblastoma HepG2 cells [31]. In 4T1 human breast cancer cells, oridonin inhibited cellular proliferation, migration, and invasion via a negative modulation of notch1-4.…”
Section: Oridoninmentioning
confidence: 99%
“…4B, the Bax/Bcl-2 ratio of compound 23 treated HepG2 cells increased obviously, which always resulted in the activation of caspases and led to apoptosis. 28 However, it made no difference for Bax/Bcl-2 ratio aer treated with compound 1 and 30.…”
Section: Mrna Expression In Hepg2 Cellsmentioning
confidence: 96%
“…About 40 µg of proteins was loaded into wells of an SDS-PAGE gel and were transferred to polyvinylidene fluoride membranes. These were incubated with the caspase-3 antibody and/or bcl-2 antibody at 4°C overnight 37,38 and were then incubated further with secondary antibody. β-Actin was chosen as the internal reference.…”
Section: Apoptosis Analyses Cell Cycle Assays and Migration Assessmmentioning
confidence: 99%